Factors influencing cloud accounting software adoption among Small and Medium Enterprises (SMES) in the Northern States of Malaysia - Nur Amnie, Zulkifli (2024)
In the current digital era, cloud accounting is one of the most useful tools that can be utilised by small and medium enterprises (SMEs). Many SMEs have failed to properly manage their accounting management due to the inadequate understanding and managerial skills that lead them to their dissolvement. In this study, the Technology- Organisation-Environment (TOE) framework was adopted but the researcher only applied the technology and environmental contexts. The study’s objective is to examine the influence of technology factors and government support on the influence of cloud accounting software adoption. The quantitative research approach is employed, and the accountants and management of SMEs in the northern states of Malaysia were surveyed. A total of 121 responses have been obtained and analysed. Analyses of the survey data were conducted using SPSS and PLS-SEM. The findings revealed that SMEs in Malaysia’s northern states are positively and significantly influenced by relative advantage and government support when they want to adopt cloud accounting software. Anyhow, data security and privacy concerns and compatibility were found to be insignificant on the influence of cloud accounting software adoption among SMEs in Malaysia’s northern states. Through this research, some insights will be added to the accounting literature of Malaysian SMEs and serve as a guide for those who have yet to adopt cloud accounting software. As for practical contributions, this research will help cloud accounting providers create user-friendly interfaces and improve software designs and features to meet user expectations. Other than that, this research will show government and regulatory officials how vital incentives and training support groups are for SMEs